Late modernity teachers faced with the choice of values. Dilemmas and challenges = Nauczyciele późnej nowoczesności wobec wyboru wartości. Dylematy i wyzwania - Pasterniak-Kobyłecka, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Contemporary educators of children and adolescents face the importance of the assessment of the surrounding reality and the acceptance or rejection of the ongoing changes. They are required to understand and be capable of explaining these changes to their pupils. In the group interviews made by the author, teachers spoke about their axiological preferences, what they value, approve of, and want to expand. Among the educators, especially young ones, one can notice the orientation towards new values: activity, individualism, innovation, resourcefulness, and independence. Fixed and constant values (e.g., the truth, good, and humanity) are rarely chosen.
Keywords: values; value choices; ambiguity; wartości; wybor wartości; ambiwalencja